A Micro-Scale Study of Flood Risk Assessment in Urban Fluvial Areas Using the Flood Potential Index - Tallar, Robby Yussac; Geldoffer, Golan Mauregar (Frontiers in Environmental Science, 2022)
Worldwide, increasing various methods is being offered to the issue of flood disasters in urban fluvial areas, yet there is a relative lack of micro scale study concerning the potential flood index to forecast future flood events in DKI Jakarta. Recent advances, the information of flood risk assessment can be monitored and communicated by using Flood Potential Index (FPI), embedded with Geographical Information System (GIS)-based model. Therefore, the main purpose and concerned issue in this paper is how to relate micro scale study of flood risk assessment in urban fluvial area, DKI Jakarta as the study case, by using FPI. Specific parameters were selected to develop and analyze FPI, involving three considerations: meteorological, physical-environtment, and socio-economic aspects. The classification also has been developed by the analysis of data from rainfall, Normalized Difference Vegetation Index (NDVI) obtained from Landsat 8 interpretation, and population density to produce flood potential hazard map for each sub-districts in DKI Jakarta during 2021-2024. The completed analysis of classification for each sub-district in DKI Jakarta resulted that 10 sub-districts with high potential, 219 sub-districts with medium potential, and 32 sub-districts with low potential in 2024. Our findings also confirmed that using a GIS approach in identifying and measuring the FPI in DKI Jakarta for micro scale area are very helpful in order to develop better adaptive local flood management practices. For future works, the assessment not only produces a visualization of flood potential index but also estimate possible damage due to flood hazard itself.